1985
DOI: 10.1159/000265343
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cataractogenesis in Humans and in Rats with Alloxan-Induced Diabetes

Abstract: Changes in the cation balance cause hydration and initiate the process of lens opacification. Such alterations were studied in human cataractous lenses and during the development of alloxan-induced diabetic cataract in rats by biochemical and histochemical techniques. The development of alloxan-induced cataract in rats was examined in vivo which showed cortical opacities beginning after 32 days. These opacities did progress to maturity after 64 days and finally the lenses were completely opacified after 96 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The incidence of cataract is increased in subjects with G6PDH deficiency [43]. Accordingly, human cataractous lenses showed a decrease in G6PDH activity [44]. Inactivation of these enzymes would slow down glycolysis and the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cataract is increased in subjects with G6PDH deficiency [43]. Accordingly, human cataractous lenses showed a decrease in G6PDH activity [44]. Inactivation of these enzymes would slow down glycolysis and the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that inhibition of Na+, K+-ATPase activity has been found to accelerate depletion of adenosine triphosphate (ATP), induce mitochondrial depolarization, suppress reactive oxygen species (ROS) scavenging, and enhance ROS production and oxidative stress [122,123,124]. Loss of Na+, K+-ATPase activity is associated with cataract formation [125,126,127,128,129] and age-dependent degeneration in photoreceptors [130]; suggesting a link between loss of Na+, K+-ATPase and AMD.…”
Section: Molecular and Biochemical Markers Relevant To The Pathophmentioning
confidence: 99%
“…The molecular mechanisms by which F inhibits Na+, K+-ATPase enzyme activity have recently been described [208]. As previously elucidated loss of Na+, K+-ATPase enzyme activity is associated with impaired ROS scavenging, enhanced ROS production [122,123,124], cataract formation [125,126,127,128,129] and age-dependent degeneration in photoreceptors [130]. It is long known that F is an inhibitor of the Na+, K+-ATPase enzyme activity [209,210,211,212,213,214,215,216,217,218,219,220].…”
Section: Molecular Mechanisms Underlying Fluoride Contribution To mentioning
confidence: 99%
“…In addition, it has been observed that in human patients with diabetes mellitus, activities of aldose reductase and sorbitol dehydrogenase vary with stage of the disease. 10,11 Aldose reductase activity is not increased in lenses from people with early-stage diabetic cataracts, 12,13 whereas in lenses from people with hypermature or senile diabetic cataracts, increased aldose reductase activity and decreased sorbitol dehydrogenase activity have been confirmed. 10,11 The purpose of the study reported here was to measure activity of NADPH-dependent reductases, which primarily reflects aldose reductase activity, 14 and sorbitol dehydrogenase activity in lenses from healthy dogs and cats.…”
mentioning
confidence: 98%
“…10,11 Aldose reductase activity is not increased in lenses from people with early-stage diabetic cataracts, 12,13 whereas in lenses from people with hypermature or senile diabetic cataracts, increased aldose reductase activity and decreased sorbitol dehydrogenase activity have been confirmed. 10,11 The purpose of the study reported here was to measure activity of NADPH-dependent reductases, which primarily reflects aldose reductase activity, 14 and sorbitol dehydrogenase activity in lenses from healthy dogs and cats. We assumed that the ratio of NADPH-dependent reductases activity-to-sorbitol dehydrogenase activity would provide an estimation of the accumulation rate of sorbitol in the initial stages of hyperglycemia and hypothesized that the ratio for dogs would be significantly different from the ratio for cats.…”
mentioning
confidence: 98%